Sex Ratios, Sexual Dimorphism, Body-Weight and Moisture Content in Two Desert Termites, Anacanthotermes Macrocephalus (Hodotermitidae) and Microteremes Mycophagus (Termitidae), from India - Roonwal, M L; Rathoe, N S (Annals of Arid Zone, 2016)
Sex Ratios : Among 1284 swarming imagoes in Anacanthotermesmocrocephalus (Desn.) males predominate in the ratioof ♂9: ♀7.7 (range♂535-68%, ♀32-46.5%). Similarly, in Microtermes mycophagus (Desn.) among 689 imagoes, malespredominate in the ratio of ♂4.1 :♀3 (range ♂57.1-62.9%, ♀37.1-42.9%).Sexual Dimorphism: In deal ate imagoes of A. macrocephalusthe sexes do not differ in respect of either the total length(without wings) or the maximum head-width, but theabdomen is slightly wider in females than in males. Nosexual difference is noticeable in the body-weight of dealates(♂48.0-55.8 mg., ♀47.0-59.8 mg.). In M. mycophagus thetotal length (with wings) and the head-width show noappreciable sexual differences, but the total length of body(without wings) and the maximum width of the abdomenare significantly greater in females than in males. Femalesare significantly heavier than males by about 4.8 mg. (meanweight of males 23.23 mg., females 28.06 mg.). For dryweight this difference is about 2.4 mg. (mean males 13.05mg., females 15. 48 mg.). The mean moisture-content ofbody is about 43.5% of wet weight in males and 44.8 % infemales, the sexual difference being only poorly significant.In both species, no correlation was found between headwidthand total body- length (without wings).